Maternal Health in Crisis: A Scoping Review of Barriers and Facilitators to Safe Abortion Care in Humanitarian Crises - Dias Amaral, Bianca; Sakellariou, Dikaios (Frontiers in Global Women's Health, 2021)
During humanitarian crises, women are particularly vulnerable to unwanted pregnancy. Unsafe abortion is among the five leading causes of maternal mortality and it is the only one which is entirely preventable. This study aimed to identify the barriers and facilitators to the provision of safe abortion care by humanitarian organisations. We performed a scoping review of the literature in July 2020, covering the years 2010-2020, on the following databases: Medline, Global Health, CINAHL Plus and ReliefWeb. We critically appraised all included articles and we conducted a narrative synthesis of the findings. We retrieved 881 articles. After removing duplicates and excluding articles that did not meet the inclusion criteria, twenty-four articles published between 2015 and 2020 were included in the review. Nine of the included papers were non-research practice items. The findings revealed five main themes: legal environment; context; stigma; economic factors; and service delivery. Restrictive laws, stigma, and lack of funding were reported as the main barriers to safe abortion, while the main facilitators were the fact that abortion is permitted under some circumstances in most countries, humanitarian actors’ ability to inform healthcare policies at the onset of a humanitarian crisis, and community engagement. The scoping review revealed a dearth of published research. Increased dissemination of studies on Termination of Pregnancy (ToP) could increase the visibility of unsafe abortion and the need to provide ToP in humanitarian settings. Moreover, humanitarian organisations need to have a clear protocol on safe abortion and an in-depth understanding of relevant legislation, including the International Humanitarian Law, in order to provide this service to the full extent of the law.